Polyfunctional HIV-specific T cells in Post-Treatment Controllers. (24th September 2016) - Samri, Assia; Bacchus-Souffan, Charlin; Hocqueloux, Laurent; Avettand-Fenoel, Véronique; Descours, Benjamin; Theodorou, Ioannis; Larsen, Martin; Saez-Cirion, Asier; Rouzioux, Christine; Autran, Brigitte
Abstract : To further understand the exceptional HIV-1 control observed in Post-Treatment Controllers (PTCs) from the Virological and Immunological Sustained CONtrol after Treatment Interruption study we investigated their HIV-specific T-cell responses. Polyfunctionality of HIV-specific CD4 and CD8 T cells and the ratios of HIV-specific CD4 T cells per infected cells were similar in post-treatment controllers, continuously early-treated patients and long-term non-progressors Overall early treatment appears to preserve robust HIV-specific CD4 + T cells, which might contribute to the posttreatment control of HIV. Abstract : Supplemental Digital Content is available in the text